GoAk Bali: An Educational Game for Mastering Balinese Script Based on Self-Regulated Learning for Fourth-Grade Elementary School Students - Ayusadewi, Ni Nyoman; Suartama, I Kadek (Jurnal Pedagogi dan Pembelajaran, 2024)
The low interest in learning among students has resulted in poor learning outcomes, which is partly due to the lack of learning media that align with students' characteristics. This study aims to develop an educational game media based on self-regulated learning to improve the learning outcomes of Balinese language for fourth-grade elementary students. The development process follows the ADDIE model and focuses on Balinese script content. Three experts were involved in the study: one content expert, one learning design expert, and one media expert. The product was tested with 3 students in individual trials, 9 students in small groups, and 20 students in field trials. Data were collected through interviews, observations, questionnaires, and tests, and analyzed using both qualitative and quantitative methods. The results show that the expert evaluations rated the product very positively, with content expert evaluation at 92.85%, learning design expert at 98.75%, and media expert at 97.64%. The product trial results also demonstrated excellent quality, with individual testing at 90.33%, small group testing at 90%, and field testing at 91.5%. Effectiveness testing revealed a significant improvement in learning outcomes, with pretest scores averaging 47.5 and post test scores averaging 80.75. This study highlights the potential of educational game media, incorporating gamification elements, to enhance student learning outcomes, deepen the learning experience, and make learning more enjoyable.